Bucking the Party Line: Calavita's Invitation to Law & Society (In Which the Author Is Invited to a Party Where He Encounters Many Old and Familiar Faces, Becomes Argumentative, Stays Up Too Late, and Finally Departs in Search of New Adventures). Issue 1 (January 2014) - Tomlins, Christopher
<x xml:space="preserve">Abstract</x> Intended as a short survey text, Kitty Calavita's Invitation to Law & Society expertly summarizes many of the central themes of law and society scholarship as they have developed over the past fifty years. It also clearly identifies the field's object of attention: "real" law. I use this commentary on the book as an opportunity to assess the field as it enters its sixth decade. How has the field changed? What are its defining characteristics? What is "real" law? Does law and society research have a future?